Risk factors for relapse in non-infectious cryoglobulinemic vasculitis, including type I cryoglobulinemia: a systematic review - Rajendran, Nithya; Rameli, Puteri Maisarah; Awad, Hanaa (Frontiers in Immunology, 2023)
Background Data on non-infectious cryoglobulinemic vasculitis (NICV) is scarce, especially concerning the management of relapses, which are troublesome. We aimed to investigate risk factors for relapse in NICV. Methods A systematic literature search of CINAHL, Embase, MEDLINE, Scopus, and the Web of Science databases was implemented until April 2023. Eligible studies included randomized control trials, observational studies, and case series with ≥4 patients. Two reviewers independently extracted data and assessed the quality of the eligible studies. Results A total of 3,724 articles were retrieved from a database search, with 27 studies meeting the inclusion criteria for review. Most studies (n = 23) detailed relapses, with the time to relapse varying between 1 and 80 months. The relapse rate was reported at 28% in Type I NICV and ranged from 22% to 60% in mixed NICV. Risk factors for relapse in NICV were identified based on the cryoglobulin subtype and correlated with clinical and immunological responses to varying treatment regimens. Type I NICV with an associated lymphoproliferative disorder exhibited a response-relapse pattern. Cutaneous and articular involvement and incomplete clinical and immunological responses to treatment, particularly corticosteroid monotherapy and occasionally rituximab, influence the risk of relapse in Type II and Type III NICV. Conclusion Our findings underscore the significance of attaining both clinical and immunological responses and identifying risk factors for relapse in NICV. Appropriate risk stratification for NICV patients is essential for the successful implementation of effective treatment strategies. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023408140.